Impact of adverse events on patient outcomes in a Japanese intensive care unit: a retrospective observational study - Gen Aikawa; Akira Ouchi; Hideaki Sakuramoto; Chiemi Ono; Chie Hatozaki; Mayu Okamoto; Tetsuya Hoshino; Nobutake Shimojo; Yoshiaki Inoue (Wiley, 2021)
Abstract Aim We investigated adverse events (AEs) in a Japanese intensive care unit (ICU) and evaluated the impact of cause‐specific AEs on mortality and length of stay. Design A retrospective observational study in the ICU of an academic hospital. Methods We reviewed medical records with the Global Trigger Tool. Results Of the 246 patients, 126 (51%) experienced one or more AEs with an incidence of 201 per 1000 patient‐days and 115 per 100 admissions. A total of 294 AEs were detected with 119 (42%) adverse drug events, 67 (24%) procedural complications, 63 (22%) surgical complications, 26 (9%) nosocomial infections, 5 (2%) therapeutic errors and 4 (1%) diagnostic errors. Adverse event (AE) presence was associated with length of ICU stay (β = 2.85, 95% confidence interval [CI]: 1.09-4.61). Adverse drug events, procedural complications and nosocomial infections were strongly associated with length of ICU stay (β = 2.38, 95% CI: 0.77-3.98; β = 3.75, 95% CI: 2.03-5.48; β = 6.52, 95% CI: 4.07-8.97 respectively).